1991
DOI: 10.1192/bjp.158.1.64
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis of Depression in Old Age

Abstract: The 12-month outcome of 103 elderly depressed patients treated by psychiatrists in Perth, Western Australia, was good in 32-47% of cases, depending upon the stringency of the outcome criteria used. A higher than expected mortality was found, especially in men. No clear association was found between 12-month outcome and a variety of clinical variables at index admission, including chronic physical illness, severity of depression, and severe life events during follow-up. As the statistical power of this and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 27 publications
7
63
3
Order By: Relevance
“…In two further UK studies, of inpatients only, the figures were 53% (Post, 1972) and 44% (Baldwin and Jolley, 1986). In Australia, Burvill et al (1991) found that 35% of their depressed group, mainly inpatients, were deluded. In the USA, Meyers and Greenberg (1986) reported that 45% of their 161 patients, consecutively admitted, were deluded.…”
Section: Discussionmentioning
confidence: 93%
“…In two further UK studies, of inpatients only, the figures were 53% (Post, 1972) and 44% (Baldwin and Jolley, 1986). In Australia, Burvill et al (1991) found that 35% of their depressed group, mainly inpatients, were deluded. In the USA, Meyers and Greenberg (1986) reported that 45% of their 161 patients, consecutively admitted, were deluded.…”
Section: Discussionmentioning
confidence: 93%
“…In all, 70-80% of the study participants responded to treatment (with about half ultimately remitting) but differed in how long they took to respond. Both the high rates of response and the similarity of categorical outcomes among the three groups may be attributable to the high-intensity, systematic treatment regimen (paroxetine, interpersonal psychotherapy, and drug augmentation, if appropriate), as also reported in a prior study (Burvill et al, 1991). Additionally, patients with recurrent depression (regardless of age of onset) were more likely to require at least one augmenting agent to achieve stabilization, thus accounting for their longer time to response (4 weeks on average).…”
Section: Treatment Response Variability (Table 2 Figure 1)mentioning
confidence: 84%
“…It may, therefore, modify the otherwise unfavorable impact that chronic physical illnesses are known to have on the presentation and prognosis of depression (Murphy, 1983;Baldwin and Jolley, 1986;Burvill et al, 1991;Meats et al, 1991).…”
Section: Introductionmentioning
confidence: 98%